Fatigue behavior of freestanding AA2024 and AAA7075 cold spray deposits. (July 2018) - White, B.C.; Story, W.A.; Brewer, L.N.; Jordon, J.B.
Highlights: Fatigue of cold spray normalized by strength compared well to the control. Fatigue crack initiation was found to originate from Cold spray interlayer defects. AA7075 had fewer interlayer defects and longer fatigue life than AA2024. Abstract: This paper examines the fatigue properties of freestanding AA7075 and AA2024 Cold Spray (CS) deposits. In this study, high pressure cold spray was used to make deposits large enough to machine mechanical test specimens free from the substrate. To quantify the mechanical performance, monotonic tensile and stress-controlled fatigue experiments were carried out on the freestanding CS and wrought AA7075 and AA2024 specimens. The experimental fatigue results revealed a reduction in the stress-life behavior of the CS deposits compared to the corresponding wrought material. However, when normalized by their ultimate tensile strengths, the CS specimens compared very well with the wrought materials, especially for the CS AA7075. Post-mortem analysis of the CS specimens revealed that fatigue cracks typically initiated from layer interface defects and subsequent crack propagation was influenced by the CS prior-particle boundaries. The results from this study indicate that refining the layer interface bonding may increase the fatigue resistance of freestanding aluminum alloy CS deposits.